Policing the pandemic - Kutnjak Ivković, Sanja (Routledge, 2024)
"Policing the Pandemic explores how police agencies in United Kingdom and the United States have adjusted to their changing environments, both during the peak of the COVID-19 pandemic and later, when the restrictions have been relaxed and the societies have begun to develop their new normal. Combining interviews and surveys of police officers and police administrators from the UK and the USA, this book provides a systematic and empirically-based account of these changes and elaborates on the lessons for the future. The book offers insight into organizational and operational changes brought on by the pandemic, including the changes in their workload, enforcement activities, and administrative changes. It examines police perceptions of, and compliance with, pandemic related changes, any potential COVID-19 related training, and the frequency with which they used various responses when observing violations of COVID-19 regulations and laws. It also focuses on police officers' own fear of contracting COVID-19, whether they had been diagnosed with COVID-19, and how the pandemic affected their own health, stress, and general well-being. This book is an essential reading for scholars, policymakers, and police administrators tackling issues such as procedural justice, organizational change, and police officer well-being, as well as those more widely engaged with societal and legal consequences of the pandemic, be it the COVID-19 pandemic or any future pandemics"--